2019
DOI: 10.3324/haematol.2019.225060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a miR-146b-Fas ligand axis in the development of neutropenia in T large granular lymphocyte leukemia

Abstract: wordsMain text: 3380 words

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Increased FasL on cancer cells counterattacks immune cells, induces immune cell death, and eventually promotes cancer immune privilege [114]. In T cell large granular lymphocyte leukemia, it was found that STAT3-induced miR-146b loss led to increased FasL expression and potential neutropenia [115]. Besides, the miR-768-3p mimic treatment in NSCLC cell immensely increased FasL level but decreased Fas expression on cancer cells [116].…”
Section: The Mirnas and Tumor-mediated Immune Cell Deathmentioning
confidence: 99%
“…Increased FasL on cancer cells counterattacks immune cells, induces immune cell death, and eventually promotes cancer immune privilege [114]. In T cell large granular lymphocyte leukemia, it was found that STAT3-induced miR-146b loss led to increased FasL expression and potential neutropenia [115]. Besides, the miR-768-3p mimic treatment in NSCLC cell immensely increased FasL level but decreased Fas expression on cancer cells [116].…”
Section: The Mirnas and Tumor-mediated Immune Cell Deathmentioning
confidence: 99%
“…We hypothesized that the mechanism accounting for neutropenia development involves high levels of STAT3 activation (14). More in detail, we recently demonstrated the presence of a STAT3-miR-146b-FasL axis in neutropenic T-LGLL patients, that, once triggered, leads to high production of Fas Ligand, which in turn is responsible of neutrophil apoptosis (51). These data emphasize the role of STAT3 activation in the pathogenesis of LGLL neutropenia, with STAT3 mutations likely being involved in further boosting this mechanism.…”
Section: The Clinical Impact Of Stat3 and Stat5b Mutationsmentioning
confidence: 99%
“…Intriguingly, miR-146b resulted to be down-regulated in T-LGL of neutropenic patients, due to a hypermethylation of its promoter. Of note, a direct role of STAT3 activation was suggested in this epigenetic alteration, by promoting the DNA methyltransferase 1 (DNMT1) expression [12].…”
Section: Novel Insights In Fasl Regulation: the Stat3/mir-146b/fasl Axismentioning
confidence: 99%
“…Herein, we will discuss the putative pathogenetic hypotheses and mechanisms accounting for neutropenia development, particularly the recent identification of a microRNA(miR)-146b defective expression in leukemic T-LGL [12]. Moreover, we will focus on both current therapies and novel promising strategies for the treatment of neutropenic LGLL patients.…”
Section: Introductionmentioning
confidence: 99%